Likelihood ratio tests for a unit root in panels with random effects. Issue 3 (4th May 2017) - Larsson, Rolf; Lyhagen, Johan; Westerlund, Joakim
ABSTRACT: Because of the fixed heterogeneity of their models, most panel unit root tests impose restrictions on the rate at which the number of time periods, T, and the number of cross-section units, N, go to infinity. A common example of such a restriction isN / T → 0, which in practice means thatT ≫ N, a condition that is not always met. In the current paper the heterogeneity is given a parsimonious random effects specification, which is used as a basis for developing a new likelihood ratio test for a unit root. The asymptotic analysis shows that the new test is valid for all( N, T ) expansion paths satisfyingN / T 5 → 0, which represents a substantial improvement when compared to the existing fixed effects literature.